Adding Spatial Context to the April 17, 1975 Evacuation of Phnom Penh: How Spatial Video Geonarratives Can Geographically Enrich Genocide Testimony. Issue 2 (3rd July 2019) - Curtis, Andrew; Tyner, James; Ajayakumar, Jayakrishnan; Kimsroy, Sokvisal; Ly, Kok-Chhay
Abstract : Between 1975 and 1979, upwards of two million men, women, and children perished from starvation, disease, exhaustion, inadequate medical care, torture, murder, and execution during the Cambodian genocide. Within this context, the forced evacuation of Phnom Penh has figured prominently in the literature, especially with regard to the violence encountered on the route. To date, however, there has been no empirical reconstruction of the evacuation. Here we address this deficiency, while simultaneously presenting a novel geospatial approach that can be utilized to collect, map and analyze interviews in a more appropriate manner than by more traditional geographic information systems (GIS) use. We utilize a spatial video geonarrative to provide a geographically-supported reconstruction of the forced evacuation of Phnom Penh through the collection of first-hand accounts taken while retracing the route. We add previously unavailable, contextualized, spatial insights to this forced evacuation, including findings on why the bridges acted as choke points, leading to increased violence. Moreover, in some instances the direction of the march turned back towards the city because of the road configuration which again led to a choke point as two columns merged. In presenting these types of contextualized, spatial details we contribute to both the specifics of the Cambodian genocide, and to how thick mapping and inductive visualization can enrich similar research in the humanities